The Fonte Gaia from Renaissance to Modern Times : a History of Construction, Preservation, and Reconstruction in Siena - Scappini, Chiara E. (Amsterdam University Press, 2018)
Intro; The Fonte Gaia from Renaissance to Modern Times; Table of Contents; Illustrations; Abbreviations; Acknowledgments; Preface; 1. Siena: Water and Power; Water; Early Medieval Italian Fountains; Sienese Fountains; 2. The First Fonte Gaia; The Contract for the First Fountain; Decoration of the First Fountain; Sources of Water for the Fountain; The History of the First Fountain; Jacopo della Querciaâ#x80;#x99;s Fonte Gaia and Its Chronology; Identifying the Fonte Gaiaâ#x80;#x99;s Parapet Sculptures; Acca Larentia and Rhea Silvia; Jacopo della Querciaâ#x80;#x99;s Parapet Statues; Mother Earth and Gaia